Intestinal Parasitic Infections between Patients Attended to Soba University, Khartoum, Sudan, July-September 2016 (Global Journal of Medical Research, 2018)
Background: Intestinal parasitic infections are amongst the most common infections throughout the world. It is estimated that some 3.5 billion people are affected, and that 450 million are ill as a result of these infections, the majority being children. Rationale: Intestinal parasitic infections lead to nutritional deficiency and impaired physical developments which will have negative consequences on cognitive function and learning ability. Objective: To detect prevalence of intestinal protozoa among patients attended to soba university hospital during the period of the study. Material and Method: Descriptive, cross sectional study, stool specimens were collected from 113 patients attended to Soba university hospital and examined by wet preparation and concentration techniques. Discussion: Our result represent that the level of sanitation is moderate compared with other studies mentioned above, but we need to perform stool concentration methods to confirm this suggestion. Result: 15.92% of stool specimens examined were positive for intestinal parasites. Conclusion: Further studies are required with large sample size, long duration and stool concentration techniques.
Keywords: prevalence; intestinal parasites; patients